ANALISIS PHYSICAL DISTANCING, KEPERCAYAAN KEAMANAN PADA MINAT BELI, MODERASI PEMBAYARAN ATOME - Koerniawan Hidajat; Fais Datul Fidad Nurul Islam (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
The shopping center at the sunter brick shop experienced a decline in purchases and sales during the Covid-19 pandemic, entering the new normal, experiencing a change in shopping. The purpose of this research is to fulfill trust and make positive use of technology. Casual associative quantitative research method and data obtained from questionnaires. The results of the study show that entering the new normal is a step for consumers to shop during the pandemic. Since its implementation, physical distancing has been in the rules of the Indonesian government and its policies. Changes in people's lifestyles to gain consumer trust by providing good quality and especially convenience in direct shopping, therefore each outlet is a reason to be able to move with ease of payment to support changes during the COVID-19 pandemic.